USP39 phase separates into the nucleolus and drives lung adenocarcinoma progression by promoting GLI1 expression - Shaoxuan Cheng; Zhiyuan Qiu; Ziyi Zhang; Yuxuan Li; Yue Zhu; Yuxin Zhou; Yinghui Yang; Yaowen Zhang; Dian Yang; Yingqiu Zhang; Han Liu; Zhaoxia Dai; et al. (Cell Communication and Signaling)
Abstract Background Intracellular membraneless organelles formed by liquid-liquid phase separation (LLPS) function in diverse physiological processes and have been linked to tumor-promoting properties. The nucleolus is one of the largest membraneless organelle formed through LLPS. Deubiquitylating enzymes (DUBs) emerge as novel therapeutic targets against human cancers. However, the nucleolar phase separation of DUBs and association with lung cancer development have remained incompletely investigated till now. Methods GFP-USP39 fusion proteins were analyzed for LLPS properties using immunofluorescence, fluorescence recovery after photobleaching (FRAP) and in vitro LLPS assays. Intrinsically-disordered regions of USP39 were analyzed by PhaSepDB database. Transcriptomic profiling, Western blot, RT-PCR and luciferase reporter assays were conducted to identify targets regulated by USP39. The effects of USP39 depletion on tumor progression were tested using doxycycline-inducible USP39 knockdown and rescue lung adenocarcinoma cells both in vitro and in vivo by performing MTT, colony formation, EdU staining, transwell and tumor xenograft model experiments. Results USP39 phase separates into nucleoli depending upon its N-terminal disordered region with amino acid residues 1-103. Lung cancer cell growth and migration were dramatically inhibited by USP39 knockdown, which was rescued by exogenous USP39 complementation. Moreover, knockdown of USP39 reduced oncogenic transcription effector GLI1 levels. Finally, USP39 downregulation restricted the formation of lung cancer xenografts in nude mice. Conclusions USP39 undergoes LLPS in the nucleolus and promotes tumor progression by regulating GLI1 expression. Downregulation of USP39 effectively suppressed lung cancer growth, and therefore targeting USP39 provides novel therapeutic strategy to treat lung cancer.